An analysis of foreign body ingestion treatment below the pylorus in children. Issue 38 (September 2017) - Wu, Wei; Lv, Zhibao; Xu, Weijue; Liu, Jiangbin; Sheng, Qingfeng
Abstract : Abstract: We retrospectively studied records of patients who received conservative therapy or surgical operation for ingested foreign body (FB) located below the pylorus, and aimed to analyze the different treatment methods including prevention or operation of foreign bodies (FBs) when we found them in children of different age. The records of 16 patients (11 men and 5 women) who were hospitalized for FB ingestion between 2011 June and 2014 June were evaluated retrospectively. Mean age of the patients was 5.5 years (65.9 ± 61.0 mo). Nine patients underwent operations and 7 patients received conservative therapy. Approximately, 75% of the patients or their families recorded a positive FB swallow history. According to the results of plain radiographs, 81% patients had positive FB findings. Five patients experienced intestinal perforation. The mean duration of hospitalization was 9.13 ± 6.29 days. Intestinal perforation due to FBs is uncommon but needs to be taken into consideration especially when the FB is a magnet. It is not appropriate to give whole nuts to children (age <2 years). Radiographs should be taken 6 to 12 hours apart, and vital signs should be observed when observing a child who has ingested a sharp FB. Lastly, our society should pay more attention to psychotherapeutic needs in prepubertal children.